Pengaruh Tingkat Pendidikan, Love of Money dan Moral Reasoning Pada Persepsi Etis Mahasiswa Akuntansi - Puspita Dharmayanti, Ni Kadek Sri; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p16, 2019)
This study took the sample of all active students in the 2016 diploma program, undergraduate accounting undergraduate 2015, PPAK batch 2018, and postgraduate accounting for 2017 Faculty of Economics and Business, Udayana University using probability sampling method with random techniques. Based on the results of calculations with the Slovin formula obtained a sample of 167 people. Data collection in this study using online questionnaire techniques. The results showed that accounting students with a high level of education would also have high perceptions. Accounting students with a high level of love of money will have a low ethical perception. Accounting students with high levels of moral reasoning will have high ethical perceptions. Ethical perception will influence the ethical behavior of accounting students. This means that a high level of education and a high level of moral reasoning will enhance the ethical perceptions of accounting students, while the high level of love of money will affect the low ethical perceptions of students. Keywords : Accounting; Love Of Money; Students; Perception; Moral Reasoning.